2015
DOI: 10.1128/jb.00304-15
|View full text |Cite
|
Sign up to set email alerts
|

ABC Transporter Required for Intercellular Transfer of Developmental Signals in a Heterocystous Cyanobacterium

Abstract: In the filamentous cyanobacterium Anabaena, patS and hetN encode peptide-derived signals with many of the properties of morphogens. These signals regulate the formation of a periodic pattern of heterocysts by lateral inhibition of differentiation. Here we show that intercellular transfer of the patS-and hetN-dependent developmental signals from heterocysts to vegetative cells requires HetC, a predicted ATP-binding cassette transporter (ABC transporter). Relative to the wild type, in a hetC mutant differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 46 publications
(87 reference statements)
0
25
0
Order By: Relevance
“…Epistasis analysis similar to that done here for sepJ and patS or hetN has been recently performed for hetC and patS or hetN . The results of these analyses are consistent with the idea that the HetC ABC exporter participates in export from proheterocysts of the PatS morphogen (Corrales‐Guerrero et al ., ) or of the PatS morphogen and a HetN‐dependent signal (Videau et al ., ). The existence of a transporter specific for export of the regulators from the (pro)heterocysts to their neighboring vegetative cells could make transfer not limited to a SepJ‐dependent pathway.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Epistasis analysis similar to that done here for sepJ and patS or hetN has been recently performed for hetC and patS or hetN . The results of these analyses are consistent with the idea that the HetC ABC exporter participates in export from proheterocysts of the PatS morphogen (Corrales‐Guerrero et al ., ) or of the PatS morphogen and a HetN‐dependent signal (Videau et al ., ). The existence of a transporter specific for export of the regulators from the (pro)heterocysts to their neighboring vegetative cells could make transfer not limited to a SepJ‐dependent pathway.…”
Section: Discussionmentioning
confidence: 97%
“…Based on expression of a P hetR ‐ gfp transcriptional fusion in a sepJ ( fraG ) background, it has been suggested that SepJ is not needed for proper heterocyst pattern formation (Nayar et al ., ). However, the results described in this work and those of other recent studies (Corrales‐Guerrero et al ., 2014b; 2015; Videau et al ., ) have unraveled possible relations between SepJ and PatS and HetN, as well as between HetC and PatS and HetN, affecting heterocyst pattern formation. Heterocyst differentiation aborts early in sepJ (Flores et al ., ; Nayar et al ., ) and hetC (Khudyakov and Wolk, ; Xu and Wolk, ) inactivation mutants, an effect that could result from accumulation of inhibitory PatS that is not exported from proheterocysts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Media for Anabaena growth on ammonia as the nitrogen source was prepared as previously described (47). Heterocyst percentages were determined as previously described, and all results are expressed as the average of three replicates ± SD (48). The vegetative cell interval between heterocysts was determined by counting 300 intervals as previously described (47).…”
Section: Methodsmentioning
confidence: 99%
“…Transposon mutagenesis, screening for mutants unable to grow diazotrophically, and determination of the transposon insertion site were performed as previously described (31,32). The ability of strains to grow diazotrophically was assessed visually following 2 weeks of growth on BG-11 medium lacking a combined nitrogen source as previously described (33). Expression from the copper-inducible petE promoter was achieved with the addition of copper to a final concentration of 2 M (34).…”
Section: Methodsmentioning
confidence: 99%